Buckling and Post-buckling of Sandwich Plate with Functionally Graded Graphene Origami Reinforced Core Layer in Hygrothermal Environment - Minh Anh, Vu; Dat, Ngo Dinh; Duc, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics; Vol 39 No 4DO - 10.25073/2588-1124/vnumap.4866, 2023)
The buckling and post-buckling of magneto-electric-elastic (MEE) sandwich plate are presented. The core layer consists of epoxy matrix reinforced with graphene origami auxetic metal-material in which the volume fraction of graphene origami is assumed to vary the thickness direction in three different distributions. For MEE face sheets, the proportions of ferroelectric and ferromagnetic components are chosen equally. The Reddy's higher order shear deformation plate theory forms the basis for establishing the governing equations. The axial compressive loading- deflection amplitude relation and the expression of critical buckling loading are obtained through the application of Galerkin method. The method's accuracy is validated by comparing its results with those published by other authors. The influences of various parameters on the buckling and post-buckling of the sandwich plate are investigated in details.